PROBLEM WITH SHIFT CONDITION FOR A SECOND KIND DEGENERATED EQUATION OF HYPERBOLIC TYPE (Scientific journal of the Fergana State University, 2023)
This paper examines a displacement problem for a second  kind equation of  hyperbolic type.